Spectral-luminescent properties of siliceous films and powders activated with [Ce3+O8H:Tb3+] nanoparticles - Malashkevich, G.E.; Semkova, G.I.; Amelyanovich, O.L.; Kochubeyeva, T.G. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Nano- and microparticles of cerium dioxide having a cubic lattice with space group Fm3m, whose Ce4+ ions are partially substituted for Tb4+ and Tb3+ ions, are formed in the siliceous films and powders obtained with the help of the sol–gel technique. It is shown that saturation of the media with hydrogen leads to efficient sensitized luminescence from the 5D4 state of Tb3+ ions due to the transfer of excitations from Ce3+ ions.
Optica Applicata, Vol. 38, 2008, nr 1, s. 57-63
Keywords: optyka; cerium dioxide nanoparticles; luminescence; transfer of excitations